Universal Testing of all Pregnant Women for COVID-19: A Way Forward for Comprehensive Antenatal Care - Divakar, Hema; Narayanan, Poorni; Singh, Rita; Jyothi Girish, Divakar Gubbi (International Journal of Innovative Research in Medical Science, 2020)
The COVID-19 global pandemic has placed undue stress on health systems all around the world. However, little is known about the impact of exposure to the virus on growing foetuses or the course of COVID-19 in pregnant women, who are often asymptomatic. To develop effective policies and recommendations, robust data for both asymptomatic and symptomatic pregnant women is crucial. This can only be acquired through universal testing of all pregnant women for COVID-19. The acquired data will not only enhance our ability to answer questions around negative obstetric outcomes, such as miscarriages and preterm labours, but also lead to enhanced contact tracing, which will slow the spread of COVID-19.